Menggali Efektivitas Bantuan Langsung Tunai dalam Membantu Masyarakat - M Adi Pratama Putra; Alfinda Adellia Dirli; Wilda Andriani; Reza MauldyRaharja (Concept: Journal of Social Humanities and Education, 2023)
Direct Cash Assistance (BLT) is a significant policy instrument in efforts to alleviate poverty and improve community welfare. This article focuses on an in-depth analysis of the effectiveness of BLT as a social policy tool. The aim of this research is to evaluate the impact of BLT on recipient communities and examine the key aspects that influence its effectiveness. This research includes literature analysis and empirical data to measure the impact of BLT on poverty levels, access to education, health and other social aspects. The research results show that BLT has great potential in reducing poverty and increasing people's access to basic services. However, the effectiveness of BLT is also related to factors such as program design, recipient selection, and distribution mechanisms. This article also discusses challenges in implementing BLT, such as administrative costs and policy issues. In addition, this article provides an overview of how BLT can be integrated into a broader social policy context. In its conclusion, this research highlights the important role of BLT in helping economically vulnerable communities. However, the success of BLT depends on careful and evidence-based implementation, as well as good coordination with other social policies. This article makes a significant contribution to the understanding of the effectiveness of BLT as an important social policy instrument.